2020
DOI: 10.1108/jm2-07-2019-0159
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of a Malaysian pharmaceutical warehouse supply chain by integrating value stream mapping and discrete event simulation

Abstract: Purpose Lean implementation is vastly incorporated in core manufacturing processes; however, its applicability in the supply chain and service industry is still in its infancy. To acquire performance excellence and thrive in the global competitive market, many firms are adopting newer methodologies. But, there is a stringent need for production simulation systems to analyze supply chains both inbound and outbound. The era of face validation is slowly disappearing. Lean tools and procedures that provide future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 69 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…This study found that LSP's attraction to offers CLSC is generated from positive income due to the lower number of providers and level of competition (Tan & Li, 2018), derived from the e-commerce phenomenon were forcing the traditional retailers to closed down their stores and that vacant location is replaced with the F&B retailers (Zhang et al, 2016), changes in consumer's habits like increasing for the consumption of frozen food and ready to-eat-meal which sees the used for more CLSC to delivers these products to retail stores (Al Theeb et al, 2020;Khan & Ali, 2021), demand from customers, organisation readiness, and government regulation. In the future, it is expected that the demand will increase mainly derived from the halal and pharmaceutical sectors (Abideen & Mohamad, 2020;Abideen & Mohamad, 2019;Khan et al, 2019;Rahman et al, 2018). For the time being, the market competition is modest as the LSPs need to be ready for their capital investments, ability to invest in cold chain assets and related certifications for increasing the competitiveness level which seems too high for smaller companies.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that LSP's attraction to offers CLSC is generated from positive income due to the lower number of providers and level of competition (Tan & Li, 2018), derived from the e-commerce phenomenon were forcing the traditional retailers to closed down their stores and that vacant location is replaced with the F&B retailers (Zhang et al, 2016), changes in consumer's habits like increasing for the consumption of frozen food and ready to-eat-meal which sees the used for more CLSC to delivers these products to retail stores (Al Theeb et al, 2020;Khan & Ali, 2021), demand from customers, organisation readiness, and government regulation. In the future, it is expected that the demand will increase mainly derived from the halal and pharmaceutical sectors (Abideen & Mohamad, 2020;Abideen & Mohamad, 2019;Khan et al, 2019;Rahman et al, 2018). For the time being, the market competition is modest as the LSPs need to be ready for their capital investments, ability to invest in cold chain assets and related certifications for increasing the competitiveness level which seems too high for smaller companies.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The study reported that keeping milk in clean containers at refrigerated temperatures immediately after the milking process might delay the onset of initial microbial load and prevent the multiplication of micro-organisms, specifically between milking at the farm and transportation to the processing plant. Demand from the pharmaceutical sectors also vital in Malaysia, where some of the raw materials used need cold storage and special attention immediately (Abideen & Mohamad, 2020;Abideen & Mohamad, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This framework also indicates that the present simulation software tools must inculcate direct parametric variables that could quantify a lean tool or a lean procedure empirically in terms of simulated graphs. A separate window panel for inserting the desired performance metrics or lean benchmarks covering the scope of the given system under study is an absolute necessity (Abideen and Mohamad, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Simulation is a best-suited complementary tool for integrating with value stream mapping (VSM) technique (Abideen and Mohamad, 2020). It enables us to visualize a production line under excessive stocks and buffers and simple concept such as first-in-first-out can be applied to avoid bottlenecks.…”
Section: Overview Of Lean Simulationsmentioning
confidence: 99%
See 1 more Smart Citation